Adjuvant NY-ESO-1 vaccine immunotherapy in high-risk resected melanoma: a retrospective cohort analysis. Issue 1 (18th May 2018) - Lattanzi, Michael; Han, Joseph; Moran, Una; Utter, Kierstin; Tchack, Jeremy; Sabado, Rachel Lubong; Berman, Russell; Shapiro, Richard; Huang, Hsin-Hui; Osman, Iman; Bhardwaj, Nina; Pavlick, Anna C.
Abstract : Background: Cancer-testis antigen NY-ESO-1 is a highly immunogenic melanoma antigen which has been incorporated into adjuvant vaccine clinical trials. Three such early-phase trials were conducted at our center among patients with high-risk resected melanoma. We herein report on the pooled long-term survival outcomes of these patients in comparison to historical controls. Methods: All melanoma patients treated at NYU Langone Health under any of three prospective adjuvant NY-ESO-1 vaccine trials were retrospectively pooled into a single cohort. All such patients with stage III melanoma were subsequently compared to historical control patients identified via a prospective institutional database with protocol-driven follow-up. Survival times were calculated using the Kaplan-Meier method, and Cox proportional hazard models were employed to identify significant prognostic factors and control for confounding variables. Results: A total of 91 patients were treated with an NY-ESO-1 vaccine for the treatment of high-risk resected melanoma. Of this group, 67 patients were stage III and were selected for comparative analysis with 123 historical control patients with resected stage III melanoma who received no adjuvant therapy. Among the pooled vaccine cohort (median follow-up 61 months), the estimated median recurrence-free survival was 45 months, while the median overall survival was not yet reached. In the control cohort of 123 patients (median follow-up 30 months), the estimated median recurrence-free and overall survival were 22 and 58 months, respectively. Within the retrospective stage III cohort, NY-ESO-1 vaccine was associated with decreased risk of recurrence (HR = 0.56, p  < 0.01) and death (HR = 0.51, p  = 0.01). Upon controlling for sub-stage, the adjuvant NY-ESO-1 clinical trial cohort continued to exhibit decreased risk of recurrence (HR = 0.45, p  < 0.01) and death (HR = 0.40, p  < 0.01). Conclusions: In this small retrospective cohort of resected stage III melanoma patients, adjuvant NY-ESO-1 vaccine immunotherapy was associated with longer recurrence-free and overall survival relative to historical controls. These data support the continued investigation of adjuvant NY-ESO-1 based immunotherapy regimens in melanoma.